Wave Propagation and Localization in a Complex Random Potential with Power-law Correlations: A Numerical Study - Nguyen, Ba Phi; Dang, Huu Dinh (VNU Journal of Science: Mathematics - Physics; Vol 36 No 3DO - 10.25073/2588-1124/vnumap.4498, 2020)
In this paper, we investigate numerically wave propagation and localization in a complex random potential with power-law correlations. Using a discrete stationary Schrӧdinger equation with the simultaneous presence of the spatial correlation and the non-Hermiticity of the random potential in the diagonal on-site terms of the Hamiltonian, we calculate the disorder-averaged logarithmic transmittance and the localization length. From the numerical analysis, we find that the presence of power-law correlation in the imaginary part of the on-site disordered potential gives rise to the localization enhancement as compared with the case of absence of correlation. Depending on the disorder's strength, we show that there exist different behaviors of the dependence of the localization on the correlation strength.